The effects and underlying mechanism of extracorporeal shockwave therapy on fracture healing - Lv, Fuxian; Li, Zhenlan; Jing, Yuling; Sun, Liyuan; Li, Zhiwei; Duan, Haoyang (Frontiers in Endocrinology, 2023)
Shockwave is a special mechanical wave with both sound, light and mechanical properties. The energy of the shockwave is about 1000 times larger than the energy of ultrasonic wave. The shockwave therapy with the appropriate dose in the fracture site has been reported to induce angiogenesis, and to promote the expression of growth factors that facilitate the fracture healing in patients suffering from delayed union and non-union. In the early 1990s, extracorporeal shockwaves (ESW) was found to induce osteogenesis, and extracorporeal shockwave therapy (ESWT) came to be clinically accepted. ESWT is a non-invasive non-surgical widely used for the treatment of bone defects, nonunion, delayed union of fractures. Nevertheless, the mechanism underlying ESWT in the treatment of bone diseases and osteogenesis remains unclear. Over recent years, great efforts have been made by both scientists and clinicians to explore the underlying mechanism behind the healing effect of ESWT on bone fractures. In this review, we introduced the growth factors during osteogenesis induced by ESWT hoping to provide new insights in the clinical use of ESWT.Currently, most of the present ESWT researches are focusing on delayed union and ununion of fracture patients, and the ESWT has been proven to be an effective treatment of these clinical conditions. For clinicians and patients, the ESWT is less invasive and much more economical compared with surgery, however, when conservative treatment is invalid, surgery is still available. For the senior citizen, high-risk patients and those who refuses to surgery, the ESWT is a relatively good choice.